1985
DOI: 10.1037/0096-1523.11.2.209
|View full text |Cite
|
Sign up to set email alerts
|

Are selective adaptation and contrast effects really distinct?

Abstract: Although there is evidence that selective adaptation and contrast effects in speech perception are produced by the same mechanisms, Sawusch and Jusczyk (1981) reported a dissociation between the effects and concluded that adaptation and contrast occur at separate processing levels. They found that an ambiguous test stimulus was more likely to be labeled b following adaptation with [pha] and more likely to be labeled p following adaptation with [ba] or [spa] (the latter consisting of [ba] preceded by [s] noise)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
3

Year Published

1985
1985
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(60 citation statements)
references
References 36 publications
1
56
3
Order By: Relevance
“…It is notable that when the results of randomized presentation were examined for local sequential effects (Tuller et a!., 1994) by computing the conditional probability ofjudging each stimulus as a member of the same category as that of the immediately preceding stimulus and data were averaged across subjects, no systematic contrast or assimilative effects were evident. These data differed from those previously reported (see, e.g., Diehl, Elman, & McCusker, 1978;Diehl, Kluender, & Parker, 1985;Diehl et aI., 1980;Macmillan, Goldberg, & Braida, 1988), most likely because in our analysis the biasing context was drawn from the entire range of stimuli, not a restricted set.…”
Section: Discussioncontrasting
confidence: 57%
“…It is notable that when the results of randomized presentation were examined for local sequential effects (Tuller et a!., 1994) by computing the conditional probability ofjudging each stimulus as a member of the same category as that of the immediately preceding stimulus and data were averaged across subjects, no systematic contrast or assimilative effects were evident. These data differed from those previously reported (see, e.g., Diehl, Elman, & McCusker, 1978;Diehl, Kluender, & Parker, 1985;Diehl et aI., 1980;Macmillan, Goldberg, & Braida, 1988), most likely because in our analysis the biasing context was drawn from the entire range of stimuli, not a restricted set.…”
Section: Discussioncontrasting
confidence: 57%
“…In the current experiment, the initial prolonged adaptation period is skipped and listeners instead hear sequences of either one or five seconds of initial motion adaptation, followed by probe stimuli presented after different time delays. Regarding the chosen adaptor durations, it is possible that the aMAE may emerge after one second of motion adaptation ͑e.g., a single pass of a one second duration moving adaptor͒, as was discovered by Diehl et al ͑1985͒. In this case, the aMAE for one second of adaptation should be as strong as for five seconds; alternatively, the longer adaptation period may create a significantly larger bias in judgments of subsequent moving test stimuli, suggesting a more linear growth of the aftereffect with the amount of motion exposure.…”
Section: E the Present Experimentsmentioning
confidence: 70%
“…At the time, speech perception was thought to be mediated by specialized detectors which could be experimentally adapted by the repeated presentation of their corresponding phonemic features. Diehl et al ͑1985͒, however, showed that many of these effects could be created after a single presentation of the ''adapting'' phoneme and thus argued that it was the contrastive context of the adaptor and test pairing that created the shift rather than the fatiguing of dedicated phonemic feature detectors. In an interesting parallel to McAlpine and colleagues' study, Diehl, et al also showed that inserting pauses between each repetition of the stimulus during the adaptation period altered the resulting judgments of the subsequent test stimuli.…”
Section: Contrast Explanations Of Aftereffectsmentioning
confidence: 99%
“…Diehl and his colleagues consider their results to support an adaptation-level theory interpretation, another nondetection-theoretic approach, and one that is consistent with a response-bias interpretation. (For ongoing controversy about the nature of selective adaptation, see Sawusch and Jusczyk, 1981;Sawusch and Nusbaum, 1983;Sawusch and Mullennix, 1985;Diehl et al, 1985a;Diehl et al, 1985b). It is interesting to note, therefore, that an attempt to separate sensitivity from bias in the selective adaptation paradigm (Elman, 1979) located the effect in response bias.…”
Section: Effects Of Standardsmentioning
confidence: 98%